1-[2-(2-Oxo-1,3-oxazolidin-3-yl)ethyl]-4-phenyl-1H-1,5-benzodiazepin-2 (3H)-one - Ballo, D.; Ahabchane, N.H.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The seven-membered ring in the title compound, C(20)H(19)N(3)O(3), adopts a boat conformation with the two phenylene C atoms representing the stern and the methylene C atom the prow. The dihedral angle between the best plane through the seven-membered ring (r.m.s deviation = 0.358 A) and the phenyl substituent is 55.8 (1)degrees. The two rings at either ends of the ethyl chain are staggered [N-CH(2)-CH(2)-N torsion angle = 57.5 (4)degrees]